2014
DOI: 10.1107/s1399004714004234
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the nisin leader peptidase NisP revealing a C-terminal autocleavage activity

Abstract: Nisin is a widely used antibacterial lantibiotic polypeptide produced by Lactococcus lactis. NisP belongs to the subtilase family and functions in the last step of nisin maturation as the leader-peptide peptidase. Deletion of the nisP gene in LAC71 results in the production of a non-active precursor peptide with the leader peptide unremoved. Here, the 1.1 Å resolution crystal structure of NisP is reported. The structure shows similarity to other subtilases, which can bind varying numbers of Ca atoms. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…Furthermore, the recognition of a region upstream of S(Ϫ8) is not likely, given that the leader peptide is only 8 amino acids and given the presence of the secondary cleavage site. Core peptide recognition by NisP for the cleavage of the leader peptide has been suggested for nisin (7,22,45), and given the current results, core peptide structure is important for the specificity of mutacin 1140 leader peptide cleavage by LanP. Additional studies will need to be done to determine whether LanP can recognize unmodified core peptide or whether PTM enzyme modifications are important for the recognition.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the recognition of a region upstream of S(Ϫ8) is not likely, given that the leader peptide is only 8 amino acids and given the presence of the secondary cleavage site. Core peptide recognition by NisP for the cleavage of the leader peptide has been suggested for nisin (7,22,45), and given the current results, core peptide structure is important for the specificity of mutacin 1140 leader peptide cleavage by LanP. Additional studies will need to be done to determine whether LanP can recognize unmodified core peptide or whether PTM enzyme modifications are important for the recognition.…”
Section: Discussionmentioning
confidence: 82%
“…The substrate specificity of LanP varies among lantibiotics (6). In most lantibiotic systems, LanP is believed to be associated with the extracellular leaflet of the membrane and cell wall (7). Therefore, cleavage does not occur until mutacin 1140 is transported out of the cell by LanT.…”
mentioning
confidence: 99%
“…334 The C-terminal anchoring peptide can also be excised from NisP by autoproteolysis, likely freeing it from the cell wall. 335 …”
Section: Proteases and Export In Class I And Ii Lanthipeptidesmentioning
confidence: 99%
“…335 Although the sequence of the prodomain was included in the protein construct used for crystallization, the reported structure consists only of the serine protease catalytic domain composed of Ser224 through Arg566. SDS-PAGE analysis of dissolved crystals revealed that the protein had undergone proteolytic degradation in situ, facilitating crystallization of the resultant fragment consisting of residues 224–566.…”
Section: Proteases and Export In Class I And Ii Lanthipeptidesmentioning
confidence: 99%
“…In the maturation of subtilin, no specific protease has been found and the processing takes place outside the cell probably by diverse serine proteases (Corvey et al, 2003 ). The first lantibiotic protease with a resolved 3D structure, EpiP from Staphylococcus aureus , an analog of NisP, has been reported (Kuhn et al, 2014 ; Xu et al, 2014 ). On the other hand, in type II lanthipeptides, the protease domain is fused to the transporter and this protein cleaves behind a double glycine motif (Knerr and van der Donk, 2012 ).…”
Section: Introductionmentioning
confidence: 99%